2010
DOI: 10.1155/2011/142978
|View full text |Cite
|
Sign up to set email alerts
|

Semecarpus anacardium (Bhallataka) Alters the Glucose Metabolism and Energy Production in Diabetic Rats

Abstract: Glucose produced by gluconeogenesis and glycogenolysis plays an important role in aggravating hyperglycemia in diabetes, and altered mitochondrial function is associated with impaired energy production. The present study focuses on the effect of Semecarpus anacardium on carbohydrate metabolism and energy production in diabetic rats. Diabetes was induced by the administration of Streptozotocin at a dose of 50 mg/kg.b.wt. Three days after the induction, Semecarpus anacardium at a dose of 300 mg/kg.b.wt was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The present results showed a dramatic decrease in the levels of G6PDH in the liver tissue of STZ-induced diabetic rats. These results were similar to those of previous studies that also demonstrated lower G6PDH activity in diabetic tissues [3133]. It has been reported that hyperglycemia decreases the activities of hexose monophosphate shunt enzymes in diabetic animals and decreases G6PDH activity in diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
“…The present results showed a dramatic decrease in the levels of G6PDH in the liver tissue of STZ-induced diabetic rats. These results were similar to those of previous studies that also demonstrated lower G6PDH activity in diabetic tissues [3133]. It has been reported that hyperglycemia decreases the activities of hexose monophosphate shunt enzymes in diabetic animals and decreases G6PDH activity in diabetic rats.…”
Section: Discussionsupporting
confidence: 92%
“… Impaired mitochondrial function. Oxidative stress seen in diabetes and IR states increases the susceptibility of mitochondrial proteins to oxidative damage [ 54 , 55 ]. The consequences include decreased flux through the citric cycle and decreased activity of enzymes involved in BCAA catabolism.…”
Section: Etiopathogenesis Of Increased Bcaa Levels In Starvation mentioning
confidence: 99%
“…Impaired entrance of acetyl-CoA into the citric cycle results in increased production of acylcarnitines, acyl-CoAs, and ketone bodies and acidosis development. Mitochondria isolated from the liver and muscles of subjects with T1DM showed decreased respiratory chain activity and ATP production, decreased expression of oxidative phosphorylation genes, increased ROS production, and decreased activity of citric cycle enzymes [ 54 , 55 , 81 ].…”
Section: Etiopathogenesis Of Increased Bcaa Levels In Starvation mentioning
confidence: 99%
“…Medicinal plants have played a significant role in a variety of ancient traditional systems of medicine. They are rich sources of bioactive compounds and thus serve as an important raw material for drug production and have become a target for the search of new drugs [16]. The plants are the invaluable, incredible, and traditional sources for the curability of various diseases in the form of medicines.…”
Section: Introductionmentioning
confidence: 99%